Ternary CuIn7Se11: Towards Ultra‐Thin Layered Photodetectors and Photovoltaic Devices. (20th October 2014) - Lei, Sidong; Sobhani, Ali; Wen, Fangfang; George, Antony; Wang, Qizhong; Huang, Yihan; Dong, Pei; Li, Bo; Najmaei, Sina; Bellah, James; Gupta, Gautam; Mohite, Aditya D.; et al.
<x xml:space="preserve">Abstract</x> A few‐layered ternary Cu‐In‐Se compound is synthesized, the photoconductivity is measured, and 2D photovoltaic devices are fabricated. Few‐layered CuIn7Se11 has a strong photoresponse and the potential to serve as the active medium in ultra‐thin photovoltaic devices. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>